Improving learning and writing outcomes: Influence of cognitive and behavioral group awareness tools in wikis - Ollesch, Lisa; Heimbuch, Sven; Bodemer, Daniel (International journal of computer-supported collaborative learning, 2021)
Group awareness (GA) tools can facilitate learning processes and outcomes by visualizing different social attributes, such as cognitive and behavioral information about group members. To assist learning and writing in social media, combining various types of awareness information may foster learning processes due to challenges, which are difficult to address by one type of GA information alone. The systematic investigation of GA tool combinations is largely unexplored with GA information often being examined separately or intermixed. To reveal both positive and negative (interaction) effects of providing different types of GA information, we conducted a 2 × 2 between-subjects experiment with N = 158 participants. Learners were provided with a wiki learning environment and, except for the control condition, different types of GA tools involving cognitive (knowledge bars) and/or behavioral (participation bars) GA information. GA tool effects were considered at wiki selection, discussion, and article levels. Eye-tracking was used for investigating the attentional effect of the GA visualizations. The results show that both types of GA information have effects on individuals’ selection preference, more strongly with the goal to learn new content than to support other wiki collaborators, which were introduced as within goal scenarios. Also, participants provided with behavioral GA support were more engaged in wiki contributions. However, only the combination of cognitive and behavioral GA information, rather than their separate visualization, had a positive effect on resulting article quality. This highlights the need for a holistic perspective when developing GA tools to improve wiki processes and outcomes.